1988
DOI: 10.1002/path.1711560405
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between hepatocellular carcinoma, cholangiocarcinoma, and metastatic carcinoma based on immunohistochemical staining for carcinoembryonic antigen and for cytokeratin 19 on paraffin sections

Abstract: An antiserum to carcinoembryonic antigen (CEA) and a monoclonal antibody to cytokeratin 19 (CK 19) were studied for their suitability as diagnostic reagents for the differential diagnosis of primary and secondary malignant epithelial tumours of the liver, on paraffin sections. With the antiserum to CEA, positive bile canalicular structures were found in 60 per cent of the hepatocellular carcinomas. All the cholangiocarcinomas and 66.6 per cent of the metastatic carcinomas were positive for CEA, without display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 11 publications
3
46
2
Order By: Relevance
“…Immunohistochemical studies have revealed that CEA may be present among neoplastic hepatocytes, showing a bile canalicular pattern as seen in non-neoplastic parts of the liver (9,10). In those reports, polyclonal unabsorbed rabbit anti-CEA immunoglobulins was used for staining.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies have revealed that CEA may be present among neoplastic hepatocytes, showing a bile canalicular pattern as seen in non-neoplastic parts of the liver (9,10). In those reports, polyclonal unabsorbed rabbit anti-CEA immunoglobulins was used for staining.…”
Section: Discussionmentioning
confidence: 99%
“…Both HepPar-1 and polyclonal antibody against CEA show low sensitivity for poorly differentiated hepatocellular carcinoma. [19][20][21][22] In contrast, GPC3, an oncofetal antigen that is expressed in 480% of hepatocellular carcinomas, has high sensitivity for poorly differentiated hepatocellular carcinoma. [22][23][24] ARG1, a manganese metalloenzyme active in the urea cycle, has recently been identified as a sensitive and specific hepatocellular marker, 25 and also has not been evaluated in scirrhous hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…7,8) In normal human liver, hepatocytes express CK8 and CK18, while bile duct cells also contain CK7 and CK19. [8][9][10][11] Since this CK pattern has been believed to be preserved during neoplastic transformation, HCC would be expected to express CK8 and CK18, but not CK7 or CK19. [8][9][10][11] Thus, expression of biliary-specific CK (CK7 and CK19) is widely used to distinguish ICC from HCC.…”
mentioning
confidence: 99%
“…[8][9][10][11] Since this CK pattern has been believed to be preserved during neoplastic transformation, HCC would be expected to express CK8 and CK18, but not CK7 or CK19. [8][9][10][11] Thus, expression of biliary-specific CK (CK7 and CK19) is widely used to distinguish ICC from HCC. 6,[8][9][10][11][12] Maeda et al 6) recommended that HCC with "suggestive" CC components (incomplete gland formation without mucin production) should be categorized as cHCC-CC when "suggestive" CC components are positive for biliary markers.…”
mentioning
confidence: 99%
See 1 more Smart Citation